Rancang Bangun Sistem Informasi Pencatatan Barang Inventaris Berbasis Web Pada MTS AL-ROZI - Mustani Mustani; Andi Cristian; Suhartini Suhartini (Jurnal Minfo Polgan, 2024)
Inventory is the process of recording inventory items in a particular institution or organization which is carried out in order to make it easier for an institution or organization to manage each inventory item they have. According to the Big Indonesian Dictionary (KBBI), inventory is a list of all items belonging to an institution, be it a school, office, company or government, which are used as tools for its operational activities.